Analysis of Urban Influence Sphere in Türkiye through the Reilly Gravity Model: The Period of 1970-2020 - Oguztimur, Senay; Sakarya, Adem (KARE PUBL, 2026)
This study aims to analyze the spheres of influence of urban centers in T & uuml;rkiye within the framework of Reilly's gravity model. Examining the temporal variation of urban spheres of influence, the research determines this using a geographic information systems environment and an inverse distance-weighted interpolation method. In this respect, the study differs methodologically from similar research in the literature. Reilly's model, inspired by Newton's model of universal gravitation, has been applied in ten-year intervals since 1970 to determine the spheres of influence of Turkish cities. The main reason for choosing the process analysis approach is the need for a long-term data set to accurately monitor social and spatial transformations. The main variables used in the study are urban populations and road distances between provincial centers for the years 1970, 1980, 1990, 2000, 2010, and 2020. The findings are noteworthy in that they demonstrate the spatial reflections of changes in institutional structures and socio-economic approaches in T & uuml;rkiye. The most striking trends observed in urbanization dynamics over time are a significant concentration of influence in the spheres of influence of large urban centers and a loss of influence for some medium-sized cities in Anatolia. The continuous increase in & Idot;stanbul's sphere of influence, in particular, can be seen as a spatial reflection of unbalanced development strategies in T & uuml;rkyie. The Reilly model has quantitatively demonstrated that other major cities, following Istanbul, have also expanded their spheres of influence.
Keywords: Road transport; urban influence sphere; Reilly law of gravitation; T & uuml; rkiye; RETAIL GRAVITATION; TRADE; Public Administration